Spitz nevus and infliximab: association or coincidence?, - Queirós,Catarina Soares (2020)
Abstract Biological therapies, including anti-TNF agents, are important in the treatment of various chronic inflammatory diseases, including psoriasis, rheumatoid arthritis or inflammatory bowel disease. The increased use of these drugs translates into an increasing awareness of its adverse effects, which include malignancy. In this paper, we describe the case of a 28-year-old woman who developed a spitzoid melanocytic tumor after starting infliximab therapy for ulcerative colitis. The evidence for causality between anti-TNF and melanocytic proliferations is still sparse; nonetheless, treatment-associated immunosuppression seems to play a key role in this phenomenon. Therefore, a regular follow-up with a rigorous skin examination is essential in these patients. Noninvasive techniques such as dermoscopy or reflectance confocal microscopy are particularly useful diagnostic tools in these circumstances.